2020
DOI: 10.3389/fpsyg.2020.586873
|View full text |Cite
|
Sign up to set email alerts
|

Working With Infertile Couples Seeking Assisted Reproduction: An Interpretative Phenomenological Study With Infertility Care Providers

Abstract: Although most studies investigated the impact of infertility and its treatment on the couple, a small body of evidence suggested that infertility care providers may experience different sources of stress related for instance to excessive workload, the complexity of the technique, and relational difficulties with patients. The current study aimed at providing further insight into the understanding of the subjective experience of infertility care providers by highlighting their feelings and emotions, personal me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Embryologists may be required to interact with patients -and their emotions and reactions -especially in the case of poor outcomes. Proper training in communication is therefore essential (Facchin et al, 2020). Patient-centeredness, defined as 'care that is respectful of, and responsive to, individual patient preferences, needs and values"' (Leavitt, 2001), represents one of the key indicators of quality in infertility care (Dancet et al, 2013) (Figure 1).…”
Section: Current Tasks Of a Clinical Embryologistmentioning
confidence: 99%
“…Embryologists may be required to interact with patients -and their emotions and reactions -especially in the case of poor outcomes. Proper training in communication is therefore essential (Facchin et al, 2020). Patient-centeredness, defined as 'care that is respectful of, and responsive to, individual patient preferences, needs and values"' (Leavitt, 2001), represents one of the key indicators of quality in infertility care (Dancet et al, 2013) (Figure 1).…”
Section: Current Tasks Of a Clinical Embryologistmentioning
confidence: 99%
“…Studies show that work in the field of fertility involves situations that have the potential to evoke a range of feelings in physicians that may affect their own lives and professionalism [ 10 , 11 ]. Patients coping with infertility rely on the medical system to assist them [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted among fertility doctors have found that communication with patients, which includes, among other things, dealing with negative emotions, particularly when they are forced to deliver bad news, is a significant source of distress [ 16 ]. Physicians may experience such news as a personal failure and disappointment, a feeling that may be triggered repeatedly given that the success of fertility treatments is still far from guaranteed [ 11 , 17 ]. One unwelcome piece of news is the suggestion that the couple attempt to conceive through the use of egg donation.…”
Section: Introductionmentioning
confidence: 99%
“…Infertility remains a well-known public health concern that is connected to medical, psychosocial and economics burdens [1] [2]. It is a global disease that affects an average of 8% to 12% of married couples across the globe [2].…”
Section: Introductionmentioning
confidence: 99%